“Travestis em todos os lugares”: uma investigação antropológica de resistências, alianças e ativismo de/com travestis em Fortaleza - Nascimento, Amadeu Cardoso do (2022)
This research consists of an ethnography informed by the transfeminist perspective that seeks to understand the alliances, the resistance and the activism of travestis in the search for the guarantee of their social, civil and political rights. The universe studied is the city of Fortaleza, CE, specifically the spaces of alliances in which travestis resist and act. The work focuses both on the life trajectories of activists such as Janaína Dutra, Thina Rodrigues, Andrea Rossati and Dediane Souza and their heirs. Interviews with transvestites Labelle Rainbow, Silvinha Cavalleire, Yara Canta and Amanda Félix on the description of different political acts that make up the social movements of which they are or were part, subsidized our research. Taking as its fundamental inspiration the works Nascimento (2021), Jesus (2019), Oliveira (2018), Nogueira (2015) and theoretical contributions such as Butler's queer theory (2019, 2020, 2021), in addition to decolonial and postcolonial studies, we resort to analysis of documents, participant observation and interviews in order to promote a description of the constitution and present configuration of the movement in the state.